2015
DOI: 10.1016/j.socscimed.2014.07.056
|View full text |Cite
|
Sign up to set email alerts
|

When does education matter? The protective effect of education for cohorts graduating in bad times

Abstract: Using Eurobarometer data, we document large variation across European countries in education gradients in income, self-reported health, life satisfaction, obesity, smoking and drinking. While this variation has been documented previously, the reasons why the effect of education on income, health and health behaviors varies is not well understood. We build on previous literature documenting that cohorts graduating in bad times have lower wages and poorer health for many years after graduation, compared to those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
71
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(72 citation statements)
references
References 62 publications
(69 reference statements)
0
71
1
Order By: Relevance
“…In a review of prior recession findings (see Glonti et al, 2015), low educational attainment was more strongly associated with negative health outcomes during periods of economic downturns compared to before their onset. Additionally, Cutler et al, (2015) demonstrated that periods of high unemployment amplified the negative health consequences of low educational attainment. That is, educationally disadvantaged who entered the labor market during economic downturns were most likely to suffer poorer health.…”
Section: Pre-existing Vulnerability To the Great Recession: Low Educamentioning
confidence: 99%
See 1 more Smart Citation
“…In a review of prior recession findings (see Glonti et al, 2015), low educational attainment was more strongly associated with negative health outcomes during periods of economic downturns compared to before their onset. Additionally, Cutler et al, (2015) demonstrated that periods of high unemployment amplified the negative health consequences of low educational attainment. That is, educationally disadvantaged who entered the labor market during economic downturns were most likely to suffer poorer health.…”
Section: Pre-existing Vulnerability To the Great Recession: Low Educamentioning
confidence: 99%
“…Conversely, other findings indicate that the protective benefits of higher education are robust during economic downturns. A cross-national study of Europeans documented unemployment rates from 1948 to 2012 and found that higher education was especially health protective among cohorts entering the workforce during periods of high unemployment (Cutler et al, 2015). Despite selective evidence supporting subgroup differences in recession impact, a majority of studies on the health correlates of recession hardships have focused on broader population averages.…”
mentioning
confidence: 99%
“…The social causation model theorizes that education causally influences health. Mechanisms through which this occurs include better working conditions, greater sense of control, increased social capital, better labor market prospects, and improved health behaviors; such as diet, exercise, and not smoking (Cutler et al, 2015; Li & Powdthavee, 2015; Margolis, 2013; Ross & Wu, 1995; Song, 2011). Education becomes even more important across the life course, as the health consequences of educational disparities diverge across time (Cohen et al, 2013; Mirowsky & Ross, 2008).…”
Section: Education and Healthmentioning
confidence: 99%
“…A great deal of empirical evidence supports basic theoretical predictions of a negative relationship between employment opportunities and criminal activity. 1 We may also expect local labour markets to influence released prisoners based on results from an emerging literature that documents long-term detrimental effects for high school or college graduates who enter more depressed local labour markets (Kahn, 2010;Oreopoulos et al, 2012;Maclean, 2013;Cutler et al, 2015). Recently, Bell et al (2014) estimated higher rates of lifetime crime and incarceration among those who leave high school during recessions in the US and the UK.…”
mentioning
confidence: 99%